Some common fixed point results on ( psi, phi)-contraction - Mahesh Chandra Arya; N. Chandra; Mahesh C. Joshi (Boletim da Sociedade Paranaense de Matemática, 2024)
The aim of the paper is to obtain common fixed point theorems for ( psi, phi)-contraction under the generalized rational type condition in a complete metric space. Moreover, these theorems generalize recent well known results in the literature.